2020
DOI: 10.3390/toxins12050325
|View full text |Cite
|
Sign up to set email alerts
|

Screening Snake Venoms for Toxicity to Tetrahymena Pyriformis Revealed Anti-Protozoan Activity of Cobra Cytotoxins

Abstract: Snake venoms possess lethal activities against different organisms, ranging from bacteria to higher vertebrates. Several venoms were shown to be active against protozoa, however, data about the anti-protozoan activity of cobra and viper venoms are very scarce. We tested the effects of venoms from several snake species on the ciliate Tetrahymena pyriformis. The venoms tested induced T. pyriformis immobilization, followed by death, the most pronounced effect being observed for cobra Naja sumatrana venom. The act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…So far, antiprotozoal activity has been found in snake venoms from various families and genera, including Asian elapids, as well as Asian, African and American viperids, and Colubrid [ 3 , 8 ]. Together with recent findings [ 12 , 13 , 14 , 15 ], these data suggest that antiprotozoal activity may be a widespread property of snake venom.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…So far, antiprotozoal activity has been found in snake venoms from various families and genera, including Asian elapids, as well as Asian, African and American viperids, and Colubrid [ 3 , 8 ]. Together with recent findings [ 12 , 13 , 14 , 15 ], these data suggest that antiprotozoal activity may be a widespread property of snake venom.…”
Section: Introductionsupporting
confidence: 83%
“…[ 8 ], Naja nigricollis [ 19 ] and some other species, as well as metalloproteases from the venoms of B. neuwiedi [ 20 ] and B. moojeni [ 21 ]. Non-enzymatic toxins include a lectin from B. leucurus venom [ 22 ], a disintegrin from Cerastes cerastes venom [ 23 ], a small pore-forming myotoxin crotamine from Crotalus venom [ 24 ], cathelicidin-like proteins crotalicidin and batroxicidin from C. durissus terrificus and B. atrox venoms [ 25 , 26 ], a CRiSP crovirin from C. viridis [ 27 ], and cytotoxins from cobra venoms [ 14 ]. It should be noted that the antiprotozoal activity of snake toxins may partially depend on the species of protozoa studied, although such data have not yet been systematized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT13Nn was isolated from N. naja venom and purified essentially as described in [53]. The purification was performed in three steps, including gel-filtration, ion-exchange and reverse-phase high-performance liquid chromatography.…”
Section: Cytotoxin Purificationmentioning
confidence: 99%
“…Several papers describe effects of animal toxins or related peptides on microorganisms. Thus, the screening of snake venoms against protozoan Tetrahymena pyriformis revealed the high activity of cobra venoms [17]. Further analysis of the venoms showed that the active components are cytotoxins of the 3FTX family.…”
mentioning
confidence: 99%